Growth of Highly Crystalline and Large Scale Monolayer MoS2 by CVD: The Role of substrate Position. Issue 6 (6th April 2018) - Kumar, Nand; Tomar, Ruchi; Wadehra, Neha; Devi, M. Manolata; Prakash, Bhanu; Chakraverty, Suvankar
Abstract: Monolayer (ML) molybdenum disulphide (MoS2 ) is of great interest for the scientific community due to its attractive electronic, optoelectronic and mechanical properties. Synthesis of high quality and large size ML MoS2 at low cost is still a challenge. Here, the growth of large area (≈5 × 1 mm 2 ) ML MoS2 on SiO2 /Si substrate via chemical vapor deposition (CVD) method is reported. It is shown by changing the substrate position w.r.t. MoO3 precursor, that the quality and size of the ML MoS2 can be drastically tuned. Raman spectroscopy and transmission electron microscopy are performed in order to ascertain the growth and high crystallinity of MoS2 . Uniformity of MoS2 layer is adjudged by Raman mapping while atomic force microscopy is performed to determine the thickness of the layer. Kelvin probe force microscopy is performed on ML MoS2 to draw the band line up of the material. Abstract : Large area high quality monolayer (ML) MoS2 are grown on SiO2 /Si substrate by CVD method. Position of substrate plays an important role in determining the quality ML MoS2 flakes. The largest (≈500 µm × 500 µm) ML continuous flakes of highly crystalline MoS2 are realized.